Non-thermal Electroporation Ablation of Epileptogenic Zones Stops Seizures in Mice While Providing Reduced Vascular Damage and Accelerated Tissue Recovery - Acerbo, Emma; Safieddine, Sawssan; Weber, Pascal; Botzanowski, Boris; Missey, Florian; Carrère, Marcel; Gross, Robert E.; Bartolomei, Fabrice; Carron, Romain; Jirsa, Viktor; Vanzetta, Ivo; Trébuchon, Agnès; et al. (Frontiers in Behavioral Neuroscience, 2021)
In epilepsy, the most frequent surgical procedure is the resection of brain tissue in the temporal lobe, with seizure-free outcomes in approximately two-thirds of cases. However, consequences of surgery can vary strongly depending on the brain region targeted for removal, as surgical morbidity and collateral damage can lead to significant complications, particularly when bleeding and swelling are located near delicate functional cortical regions. Although focal thermal ablations are well-explored in epilepsy as a minimally invasive approach, hemorrhage and edema can be a consequence as the blood-brain barrier is still disrupted. Non-thermal irreversible electroporation (NTIRE), common in many other medical tissue ablations outside the brain, is a relatively unexplored method for the ablation of neural tissue, and has never been reported as a means for ablation of brain tissue in the context of epilepsy. Here, we present a detailed visualization of non-thermal ablation of neural tissue in mice and report that NTIRE successfully ablates epileptic foci in mice, resulting in seizure-freedom, while causing significantly less hemorrhage and edema compared to conventional thermal ablation. The NTIRE approach to ablation preserves the blood-brain barrier while pathological circuits in the same region are destroyed. Additionally, we see the reinnervation of fibers into ablated brain regions from neighboring areas as early as day 3 after ablation. Our evidence demonstrates that NTIRE could be utilized as a precise tool for the ablation of surgically-challenging epileptogenic zones in patients where the risk of complications and hemorrhage is high, allowing not only reduced tissue damage but potentially accelerated recovery as vessels and extracellular matrix remain intact at the point of ablation.